Incorporating the Relation into the Language? A Survey of Approaches in Relating Logic - Estrada-González, Luis; Giordani, Alessandro; Jarmużek, Tomasz; Klonowski, Mateusz; Sedlár, Igor; Tedder, Andrew (Logic and Logical Philosophy, 2021)
In this paper we discuss whether the relation between formulas in the relating model can be directly introduced into the language of relating logic, and present some stances on that problem. Other questions in the vicinity, such as what kind of functor would be the incorporated relation, or whether the direct incorporation of the relation into the language of relating logic is really needed, will also be addressed.